The impact of transmission line terminations on radiated emissions - Wong, Wei-Juet (Curtin University, 2007)
Terminating transmission lines at either the source or the load end with a damping resistor is frequently used to improve the signal integrity of clock or control lines on printed circuit boards. While a number of termination variants may produce similar results in regards to signal integrity, the electromagnetic compatibility performance can vary due to different current and voltage distributions along the line. This thesis investigates the impact of transmission line terminations on radiated emissions.